Proposed method of identification of technical errors in artistic gymnastic - Velickovic, S.; Paunovic, M.; Madic, D.; Vukašinovic, V.; Kolar, E. (Science of Gymnastics Journal, 2016)
The aim of this study was to identify technical errors in artistic gymnastics, with comparative kinematic analysis of two gymnasts of different levels of success. The sample for comparative kinematic analysis consisted of ten attempts basket to handstand performed without technical errors by top gymnast and ten attempts performed with technical error by the middle-class gymnast. Kinematic analysis was performed with the help of 3-D video system for the APAS kinematic analysis, using a model with 17 points and 15 segments. Statistical significance of obtained mean differences between the two groups of attempts was determined using t-test for independent samples. Obtained results indicated that attempts performed flawlessly have significant greater speed of center of body gravity, point of hips and peak of feet; center of gravity of body is further away from the axis of rotation, and position of hang under is achieved with a greater angle in shoulder joint, and smaller in the hip joint; phase of front swing in hang under is realized with higher extension speed in hip joint and with expressed anti - flexion in the shoulder joint. All the above stated contributes to leave bars much later and again reach for with stretched arms, and thus there were no errors in the execution. Obtained information about the differences in performing between top gymnast and middle class gymnast have contributed to the identification of technical errors during execution and represents very important step in detection and elimination of them, generally in artistic gymnastic, not only for the specified element.